A combined experimental and DFT investigation of the adsorption of humic acid by-products on polypyrrole. Issue 9 (2nd September 2017) - Laabd, Mohamed; Atourki, Lahoucine; Chafai, Hafsa; Bazzaoui, Mohammed; Elamine, Maria; Albourine, Abdallah
ABSTRACT: This study sheds light on the removal of humic acid by-products (trimellitic and pyromellitic acids; TMA and PMA, respectively) from aqueous solution using conducting polypyrrole (PPy) as an effective adsorbent. The effects of experimental factors including contact time, solution pH, initial concentration, adsorbent dose, and temperature were systematically investigated. The pseudo-second-order kinetic model provides the best correlation with adsorption experimental data. The equilibrium adsorption was well described by the Langmuir model with maximum mono-layer adsorption capacities of 47.62 and 71.43 mg g −1 for TMA and PMA, respectively. The analysis of thermodynamic parameters indicated that the adsorption process was spontaneous and endothermic in nature. In addition, we investigated the adsorption mechanism using the density functional theory (DFT) calculations. The TMA and PMA were physisorbed on the PPy surface through the formation of hydrogen bonds between carboxylic groups of adsorbate molecules and the amino group of the adsorbent. The calculated theoretical data were in good agreement with experiments. GRAPHICAL ABSTRACT: